Whose German? : the ach/ich alternation and related phenomena in standard and colloquial - Robinson, Orrin W., 1947- (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2001)
The author addresses a number of issues in German and general phonology, using a specific problem in German phonology (the ach/ich alternation) as a springboard. These issues include especially the naturalness, or lack thereof, of the prescriptive standard in German, and the importance of colloquial pronunciations, as well as historical and dialect evidence, for phonological analyses of the "standard" language. Other important topics include the phonetic and phonological status of German /r/, the phonetic and phonological representation of palatals, the status of loanwords in phonologic.